Fire debris analysis - Stauffer, Eric, 1975- (Academic Press, 2008)
The study of fire debris analysis is vital to the function of all fire investigations, and, as such, Fire Debris Analysis is an essential resource for fire investigators. The present methods of analysis include the use of gas chromatography and gas chromatography-mass spectrometry, techniques which are well established and used by crime laboratories throughout the world. However, despite their universality, this is the first comprehensive resource that addresses their application to fire debris analysis. Fire Debris Analysis covers topics such as the physics and chemistry of fire and liquid fuels, the interpretation of data obtained from fire debris, and the future of the subject. Its cutting-edge material and experienced author team distinguishes this book as a quality reference that should be on the shelves of all crime laboratories. * Serves as a comprehensive guide to the science of fire debris analysis * Presents both basic and advanced concepts in an easily readable, logical sequence * Includes a full-color insert with figures that illustrate key concepts discussed in the text.